2021
DOI: 10.1155/2021/6307895
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Damage Constitutive Model of Anisotropic Rock: Development and Validation

Abstract: The damage constitutive model is of great significance to research the stress-strain relationship and damage evolution of rock under loading in engineering. In order to investigate the effect of anisotropic characteristic on the stress-strain relationship and damage evolution, a statistical damage constitutive model of anisotropic rock under true triaxial condition was developed. In this study, the plane which existed perpendicular to the coordinate axis was extracted from representative volume element (RVE) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This structure can result in strong anisotropy in the shale. The impact of the anisotropy of bedding on rock has been analyzed and studied by many scholars (Chandler et al, 2016;Chen et al, 2014;Geng et al, 2016;Heng et al, 2015;Ma et al, 2021;Rong et al, 2021). A statistical damage constitutive model for true triaxial conditions has been developed by Rong et al (2021), which revealed that the elastic modulus has a greater impact on strain in the same direction compared to other directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This structure can result in strong anisotropy in the shale. The impact of the anisotropy of bedding on rock has been analyzed and studied by many scholars (Chandler et al, 2016;Chen et al, 2014;Geng et al, 2016;Heng et al, 2015;Ma et al, 2021;Rong et al, 2021). A statistical damage constitutive model for true triaxial conditions has been developed by Rong et al (2021), which revealed that the elastic modulus has a greater impact on strain in the same direction compared to other directions.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the anisotropy of bedding on rock has been analyzed and studied by many scholars (Chandler et al, 2016;Chen et al, 2014;Geng et al, 2016;Heng et al, 2015;Ma et al, 2021;Rong et al, 2021). A statistical damage constitutive model for true triaxial conditions has been developed by Rong et al (2021), which revealed that the elastic modulus has a greater impact on strain in the same direction compared to other directions. In a separate study, Ma et al (2021) conducted triaxial tests on Longmaxi shale with varying bedding angles, revealing that the shale strength decreased initially but gradually increased with the increase of loading direction.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous anisotropic plastic models and damage models have been used to predict the mechanical response of anisotropic soil and rock [1][2][3][4][5][6]. Based on the framework of critical state soil mechanics (CSSM) for the triaxial space, Dafalias et al [1] have presented an anisotropic clay plasticity constitutive model.…”
Section: Introductionmentioning
confidence: 99%
“…An anisotropic elastoplastic model for soft clays has been established by Sivasithamparam and Castro [4] based on an existing model called S-CLAY1S, which is a Cam clay type model that accounts for anisotropy and destructuration. Rong et al [6] have developed a statistical damage constitutive model for anisotropic rock and accurately predicted the mechanical state and deformation of rock for geotechnical, coal mining, shale gas exploitation, etc. However, these models are described by complex formulation and parameters.…”
Section: Introductionmentioning
confidence: 99%